Benin: Internet for women civil servants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Alice Kouboura Djinadou Igue describes a project to provide computer training to women civil servants in rural areas.